“Não troco o meu Cariri por nada no mundo”: direito humano de acesso à terra e identidade territorial no assentamento Serra do Monte, Cabaceiras/PB - Aires, Renata Felinto de Farias (2019)
This study aims at analyzing the process of construction of the territorial identity of rural workers in the Serra do Monte Settlement, as a factor to strengthen the Human Right to land and to fulfill its social function. The choice of this settlement was due to its formation having occurred without the participation of social movements, a fact that brought questions about the identity relations in the territory. We use as reference the concepts of territory, territoriality and territorial identity through the authors Raffestin (1993), Haesbaert (2004), Almeida (2012) and Bonnemaison (2002). We focus on a humanistic cultural approach and an interdisciplinary perspective, as proposed by Santos (2009), Claval (2001) and Cosgrove (2003). We conducted bibliographic and documentary research and carried out fieldwork, essential for the investigation, dialoguing with Rodrigues (2007), Oliveira (2006), Marcos (2006), Kaiser (2006) and Serpa (2006). In order to reinforce the understanding of the occupation of the territory, we used social cartography as a tool, based on the readings of Gorayeb and Meireles (2014) and Acselrad (2013), using audio records, photographic documentation, field workbooks and semistructured collection instruments. We analyze the formation, the dynamics of the settlement and the relations of the diverse groups, between each other, and with the territory. We realize that access to land is still not recognized as an autonomous human right and that the brazilian Judiciary bases its decisions on the absolute defense of property. We conclude that territorial identity is a determining factor to promote and strengthen the human right to land and to provide the fulfillment of its social function, but of the five existing groups, only two demonstrate identity with the settlement. Territorial identity presented itself through the bonds created through the maintenance of its traditions, its culture, its relations with geosymbolic spaces, including its most significant memories, family bonds and for what the land provides for them, despite the difficulties faced.